Supporting groups' emotion and motivation regulation during collaborative learning. (December 2020) - Järvenoja, Hanna; Järvelä, Sanna; Malmberg, Jonna
Abstract: This study investigates when and how students activate co- and socially shared emotion and motivation regulation in collaborative learning and whether the S-REG mobile application tool can support this regulation. In a mathematics course, 44 higher education students worked with a collaborative assignment. The S-REG tool traced groups' emotional and motivational states in different sessions, and the occurrence of co-regulation and shared regulation of motivation and emotions were coded from video-recorded collaborative work (44 h). The groups activated more co-regulation than shared regulation of emotions and motivation, but the shared-regulation episodes were longer-lasting. The groups' emotional and motivational states were associated with the occurrence of co-regulation in the beginning of the learning sessions. The results suggest that the S-REG tool balanced collaboration by prompting the groups to regulate emotions and motivation right in the beginning of the motivationally and emotionally challenging learning sessions. Highlights: Collaborative group members' regulation of motivation and emotions is infrequent. Regulation in collaboration emerges throughout the learning process. Socially shared regulation takes time when activated. S-REG tool prompts groups' co-regulation when collaborative learning begins.